Ojemba Enwe Iro: An Igbo Indigenous Philosophy of Non-Hostility, Migration, and Everyday Peacebuilding - Okeke, Johnson Ifeanyi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
This article examines Ojemba Enwe Iro as an indigenous Igbo philosophical concept that articulates an ethic of non-hostility, adaptability, and peaceful coexistence in contexts of mobility and cultural plurality. The study aims to demonstrate how this moral principle functions as a culturally grounded framework for everyday peacebuilding, particularly among Igbo migrants and diasporic communities. Methodologically, the article employs a narrative review combined with hermeneutical analysis to synthesize scholarly literature on Igbo philosophy, African indigenous ethics, migration, and peacebuilding, allowing for an interpretive engagement with culturally embedded concepts. The findings reveal that Ojemba Enwe Iro operates at multiple levels as a moral guideline, a pragmatic survival strategy, and a communal expectation that governs interpersonal conduct beyond kinship and ethnic boundaries. Rooted in Igbo conceptions of personhood and communal ethics, the philosophy emphasizes restraint, relational responsibility, and adaptability as essential conditions for social harmony. The discussion further shows that this ethic is institutionalized through diaspora associations and informal governance structures, enabling conflict prevention and social integration within host communities. In dialogue with broader African philosophies such as Ubuntu, the study highlights both conceptual affinities and distinctive contributions, particularly its explicit engagement with migration and everyday peace. Overall, the article contributes to peace and conflict studies by foregrounding indigenous philosophy as a legitimate theoretical and practical resource, offering culturally responsive insights for peacebuilding, migration governance, and community relations in increasingly diverse societies.